Intercultural communication in the light of Balkan circumstances - Mujaj, Hasan; Hysenaj, Valdet (Technium Social Sciences Journal, 2024)
The aim of this research is to highlight the great importance that intercultural communication has, especially in the circumstances of multi-ethnic life not only in Kosovo, but also more widely in the Balkans, etc. As a result of this research, it appears that intercultural communication in Albanian, but also Balkan studies, has not been researched enough and deserves to be followed and advanced in the future. Intercultural communication is a wide spectrum of heterogeneous knowledge and integrated into textual wholes in different languages.